2001
DOI: 10.1074/jbc.m100085200
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Co-substrate Selectivity of Deacetoxycephalosporin C Synthase

Abstract: Deacetoxycephalosporin C synthase is an iron(II) 2-oxoglutaratedependent oxygenase that catalyzes the oxidative ring-expansion of penicillin N to deacetoxycephalosporin C. The wild-type enzyme is only able to efficiently utilize 2-oxoglutarate and 2-oxoadipate as a 2-oxoacid co-substrate. Mutation of arginine 258, the side chain of which forms an electrostatic interaction with the 5-carboxylate of the 2-oxoglutarate co-substrate, to a glutamine residue reduced activity to about 5% of the wild-type enzyme with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Mutations to residues binding the iron(II), 2-oxoglutarate, or substrate have been demonstrated to cause uncoupled turnover of 2-oxoglutarate in other enzymes, e.g. DAOCS (10,11,13,14), and this has been ascribed to the mis-alignment of this high-energy iron species with respect to prime substrate. This phenomenon probably accounts for the behavior of the Trp-82 mutants reported here, suggesting that this residue affects the binding conformation of penicillin and deacetoxycephem substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations to residues binding the iron(II), 2-oxoglutarate, or substrate have been demonstrated to cause uncoupled turnover of 2-oxoglutarate in other enzymes, e.g. DAOCS (10,11,13,14), and this has been ascribed to the mis-alignment of this high-energy iron species with respect to prime substrate. This phenomenon probably accounts for the behavior of the Trp-82 mutants reported here, suggesting that this residue affects the binding conformation of penicillin and deacetoxycephem substrates.…”
Section: Discussionmentioning
confidence: 99%
“…3), and 2-oxoglutarate co-substrate conversion (in the presence of both substrates). Both 2-oxoglutarate conversion and prime substrate oxidation (ring-expansion of penicillin G or hydroxylation of DAC) were measured as some oxygenase mutations can reduce or abolish prime substrate oxidation, whereas 2-oxoglutarate conversion can be retained ("uncoupled turnover") (10,11).…”
Section: Fig 1 Oxidative Reactions Carried Out By Daoc/dacs (C Acrmentioning
confidence: 99%
See 1 more Smart Citation
“…Henceforth, it will be easier to rationally modify the enzyme substrate preference to suit industrial needs. This has been illustrated by successful alteration of the co-substrate selectivity of scDAOCS [52]. The crystal structure of scDAOCS complexed with 2-oxoglutarate revealed that the 5-carboxylate of 2-oxoglutarate is stabilized by electrostatic interaction with the side chain of R258 [85].…”
Section: Alteration Of Deacetoxycephalosporin C Synthase Co-substratementioning
confidence: 95%
“…Replacement of Arg-36 with lysine had a similar effect as replacement with alanine, suggesting that, in addition to the positive charge at this position, the two-point interaction of the guanido group with Asp-34 is important. Chemical rescue of kinetic parameters with guanido derivatives has been reported for arginine replacement variants of several enzymes (2,8,20,21,27,29), including Cam, the prototype of the ␥-class carbonic anhydrase (39). These derivatives are thought to occupy the cavity vacated by the arginine side chain in a productive conformation which mimics the guanido group of arginine.…”
Section: Discussionmentioning
confidence: 99%